Conflict and creativity in inter-organizational teams: The moderating role of shared leadership. Issue 1 (13th February 2017) - Hu, Nan; Chen, Zhi; Gu, Jibao; Huang, Shenglan; Liu, Hefu
Abstract : Purpose: This paper aims to examine the effects of task and relationship conflicts on team creativity, and the moderating role of shared leadership in inter-organizational teams. An inter-organizational team normally comprises employees from collaborated organizations brought together to conduct an initiative, such as product development. Practitioners and researchers have witnessed the prevalence of conflict in inter-organizational teams. Despite significant scholarly investigation into the importance of conflict in creativity, a deep theoretical understanding of conflict framework remains elusive. Design/methodology/approach: A questionnaire survey was conducted in China to collect data. Consequently, 54 teams, which comprised 54 team managers and 276 team members, were deemed useful for the study. Findings: By testing our hypotheses on 54 inter-organizational teams, we found that relationship conflict has a negative relationship with team creativity, whereas task conflict has an inverted U-shaped (curvilinear) relationship with team creativity. Furthermore, when shared leadership is stronger, the negative relationship with team creativity is weaker for relationship conflict, whereas the inverted U-shaped relationship with team creativity is stronger for task conflict. Research limitations/implications: The main limitation is cross-sectional, which cannot establish causality in relationships. Despite this potential weakness, the present research provides insights into conflict, leadership and inter-organizational collaboration literature. Practical implications: The findings of this study offer some guidance on how managers can intervene in the conflict situations of inter-organizational teams. Social implications: Managers are struggling to identify ways to effectively manage team conflict when a team of diverse individuals across organizational boundaries are brought together to solve a problem. The findings of this study offer some guidance on how managers can intervene in the conflict situations of inter-organizational teams. Originality/value: This paper provides understandings about how relationship and task conflicts affect team creativity in inter-organizational teams.